2000
DOI: 10.1103/physrevlett.84.4677
|View full text |Cite
|
Sign up to set email alerts
|

Spin Fractionalization of an Even Number of Electrons in a Quantum Dot

Abstract: We find that Kondo resonant conductance can occur in a quantum dot in the Coulomb blockade regime with an even number of electrons N. The contacts are attached to the dot in a pillar configuration, and a magnetic field B( perpendicular) along the axis is applied. B( perpendicular) lifts the spin degeneracy of the dot energies. Usually, this prevents the system from developing the Kondo effect. Tuning B( perpendicular) to the value B(*) where levels with different total spin cross restores both the degeneracy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…Effects of lifting spin degeneracy of the triplet have also been theoretically investigated [14]. For the degenerate triplet case, a characteristic asymmetric peak in conductance at the ST crossing has been predicted [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of lifting spin degeneracy of the triplet have also been theoretically investigated [14]. For the degenerate triplet case, a characteristic asymmetric peak in conductance at the ST crossing has been predicted [15,16].…”
mentioning
confidence: 99%
“…The interplay of electron-electron interactions, electron spin, and coupling to a Fermi sea makes transport in the few-electron regime a subtle problem in many-body physics [12,13,14,15,16,17]. Of particular importance is the two-electron case ("quantum dot helium") [17] since this is a paradigm for the preparation of entangled electronic states [18], and in double quantum dots is the basis of a quantum gate proposal [19].…”
mentioning
confidence: 99%
“…In this case the quantum with dot a singlet ground state may become magnetically active due to external forces, and Kondo effect arises either at finite energy [19] or in external magnetic field [20][21][22]. Later on it was recognized that in many cases the direct mapping of the original Kondo model into such system is impossible, because the effective symmetry of the pertinent nanoobject is neither SU(2) nor SU(2N).…”
Section: Introductionmentioning
confidence: 99%
“…Another facet of Kondo physics in nanoobjects was unveiled, when the possibility of Kondo effect in quantum dots with even electron occupation number was considered in several theoretical publications [19][20][21][22]. In this case the quantum with dot a singlet ground state may become magnetically active due to external forces, and Kondo effect arises either at finite energy [19] or in external magnetic field [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…If N is even, the ground state (GS) of the QD is usually a spin singlet and the ordinary Kondo effect cannot occur. Nevertheless, it has been shown that level crossing between states at different S induced by a magnetic field B orthogonal to the dot can restore the degeneracy required for the Kondo effect to take place [4][5][6]. The occurrence of Kondo physics in quantum dots was predicted long ago in analogy to magnetic impurities in diluted metal alloys at very low temperatures [7].…”
mentioning
confidence: 99%